Two new species of Lobelia (Campanulaceae) from Mexico - Rzedowski, Jerzy; Calderon de Rzedowski, Graciela (Instituto de Ecología, A.C., 1997)
Lobelia diazlunae, from the Sierra Madre Occidental, and L. orientalis, from the Sierra Madre Oriental of Mexico, are described as new and illustrated. Most probably both represent very narrow endemics. The first one, collected in northeastern Nayarit, on account of its prostrate habit and solitary flowers, is similar to L.nana H.B.K. and to L. standleyi McVaugh. The second, discovered in northeastern Querétaro, in view of its superior ovary and capsule, as well of its foveolate-reticulate seeds, is related to L. tarsophora Seaton and L. hypnodes Wimmer.